Physical rehabilitation in traumatology and orthopedy. Hand injuries - Mikhalyuk, E. L.; Tkalich, I. V.; Михалюк, Євген Леонідович; Ткаліч, Ігор Вячеславович (Zaporozhye state medical university, 2011)
The educational and methodical manual is intended for independent work of students of medical faculties at preparation for practical employment on «Physical rehabilitation and sports medicine» subject
Физическая реабилитация в травматологии и ортопедии. Травмы верхней конечности